(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, the views of philosophers on the issues of family and child education. The role of family and preschool education in the socialization of children of preschool age, the important aspects of mutual cooperation between them are highlighted.